Software Architecture For Product Lines (2014)
Software product lines were designed from the product line tested out by H. Ford at the beginning of the 20 the Century, which led to the success of his automotive production. For 15 years, these methods have been visible in several software application fields: telephony at Nokia, televisions at Philips, print software at HP and flight applications at Boeing, among other. The concept of architecture is crucial for classic software applications, and this concept is even more important at the level of domain engineering in product lines. In a product line, the so-called reference architecture generically describes the architectures of all the products in the family. This chapter describes the technical means and methods for defining a reference architecture for a software product line. It will also present the methods for operating this architecture through, for example, techniques emerging from model and software component engineering, or aspect-oriented programming. These concepts and techniques will be illustrated using a case study